199k views
5 votes
Solve for y:2x – 3y = 5

User Akhil Rao
by
4.5k points

1 Answer

3 votes

y = (2x-5)/3

Step-by-step explanation:


\begin{gathered} 2x\text{ - 3y = 5} \\ To\text{ solve for y, we need to make y the subject of formula} \end{gathered}
\begin{gathered} \text{Let's take every other thing not attached to y to the right side of the equation:} \\ -3y\text{ = 5 - 2x} \\ To\text{ make y stand alone, we will divide through by -3} \\ (-3y)/(-3)=\text{ }(5-2x)/(-3) \\ y\text{ = }(-(5-2x))/(3)\text{ or }\frac{-5\text{ +2x}}{3}\text{ } \\ y\text{ = }\frac{2x\text{ -5}}{3} \end{gathered}

User Ben Kreeger
by
4.6k points